Small-Molecule Inhibitor Targeting Protein Kinase D: A Potential Therapeutic Strategy - Lv, Die; Chen, Hongli; Feng, Yun; Cui, Bomiao; Kang, Yingzhu; Zhang, Ping; Luo, Min; Chen, Jiao (Frontiers in Oncology, 2021)
The protein kinase D (PKD) family is a family of serine-threonine kinases that are members of the calcium/calmodulin-dependent kinase (CaMK) superfamily. PKDs have been increasingly implicated in multiple pivotal cellular processes and pathological conditions. PKD dysregulation is associated with several diseases, including cancer, inflammation, and obesity. Over the past few years, small-molecule inhibitors have emerged as alternative targeted therapy with fewer adverse side effects than currently available chemotherapy, and these specifically targeted inhibitors limit nonspecific toxicities. The successful development of PKD inhibitors would significantly suppress the growth and proliferation of various cancers and inhibit the progression of other diseases. Various PKD inhibitors have been studied in the preclinical setting. In this context, we summarize the PKD inhibitors under investigation and their application for different kinds of diseases.